Improving Human Wellbeing and Ecosystem Health on BC's Coast: The Challenge Posed by Historic Resource Extraction (2007)
Haida Gwaii and the Great Bear Rainforest (GBR) comprise the world’s largest intact coastal temperate rainforest. British Columbia has encouraged industrial logging of this region. As a result, ecological values have been eroded and natural capital has been drawn down. The logging industry has provided few local economic benefits. Colonization and industrial resource extraction have contributed to high levels of social distress in First Nations communities. Since 2001, logging companies, environmental organizations, and the provincial and First Nations governments have collaborated in developing an Ecosystem Based Management (EBM) approach. EBM is intended to maintain ecosystem integrity and improve human wellbeing. In 2006, the province began implementing EBM by setting aside one third of the GBR’s land base from logging and by proposing transitional EBM requirements. This paper draws on stumpage and forest cover data to analyze natural capital depletion. The analysis indicates that much of the GBR’s natural capital, as represented by timber, has been depleted. Industrial logging was already on the decline before the decision was taken to implement an EBM approach. Expectations for improved socio-economic outcomes under EBM may not be realistic given the constraints implied by past logging. If EBM performance is measured using conventional economic indicators without accounting for past depletion, it risks being found to have failed the goal of improving human wellbeing. This would create pressure to relax EBM provisions to allow more logging, an outcome that would fail both ecosystems and human communities in the long term. If much reduced extraction levels are to support local human wellbeing, a greater share of economic benefits must be retained locally.